If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (T + -4)(t + 1) = 0 Reorder the terms: (-4 + T)(t + 1) = 0 Reorder the terms: (-4 + T)(1 + t) = 0 Multiply (-4 + T) * (1 + t) (-4(1 + t) + T(1 + t)) = 0 ((1 * -4 + t * -4) + T(1 + t)) = 0 ((-4 + -4t) + T(1 + t)) = 0 (-4 + -4t + (1 * T + t * T)) = 0 (-4 + -4t + (1T + tT)) = 0 Reorder the terms: (-4 + 1T + -4t + tT) = 0 (-4 + 1T + -4t + tT) = 0 Solving -4 + 1T + -4t + tT = 0 Solving for variable 'T'. Move all terms containing T to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 1T + -4t + 4 + tT = 0 + 4 Reorder the terms: -4 + 4 + 1T + -4t + tT = 0 + 4 Combine like terms: -4 + 4 = 0 0 + 1T + -4t + tT = 0 + 4 1T + -4t + tT = 0 + 4 Combine like terms: 0 + 4 = 4 1T + -4t + tT = 4 Add '4t' to each side of the equation. 1T + -4t + 4t + tT = 4 + 4t Combine like terms: -4t + 4t = 0 1T + 0 + tT = 4 + 4t 1T + tT = 4 + 4t Reorder the terms: -4 + 1T + -4t + tT = 4 + 4t + -4 + -4t Reorder the terms: -4 + 1T + -4t + tT = 4 + -4 + 4t + -4t Combine like terms: 4 + -4 = 0 -4 + 1T + -4t + tT = 0 + 4t + -4t -4 + 1T + -4t + tT = 4t + -4t Combine like terms: 4t + -4t = 0 -4 + 1T + -4t + tT = 0 The solution to this equation could not be determined.
| -17+3x=5x+7 | | 12w+w=5-2w | | 18+2y=4y-8 | | -2x-70=29+9x | | 3(a+7)=-6 | | 7x+5x-80=136 | | 5=3x-13 | | 7y-9(5y-5)= | | 6x^2=13x-6 | | (x)+(x+2)=23 | | (M+3)-2m=3(m-3) | | 5x+67=180 | | 25x^2+30x=-9 | | 4(-4x+4)=208 | | -2x^3y+4x^2y^2+70xy^3=0 | | -15-(-2)-(11-6)= | | 4+4x=-7x-40 | | 210=10*w*3 | | 2u+18=7(u+4) | | x-5+x-5+x-5+x-5= | | 136=x^2+16X | | -10-9x=-8x+7 | | -8x+4(x-8)=-36 | | -x*6=-18 | | 3x=4-7x^2 | | 9x+7=180 | | 108+4y=-2y | | (x)+(x+2)=33 | | 6y+3=6-2y | | 5p+d*r=r-7 | | 6x-10=-70-4x | | 5(2x+61x+294)=0 |